Banking sector output measurement in the euro area - a modified approach - Antonio Colangelo; Robert Inklaar (European Central Bank (ECB), 2010)
Banks do not charge explicit fees for many of the services they provide but the service payment is bundled with the offered interest rates. This output therefore has to be imputed using estimates of the opportunity cost of funds. We argue that rather than using the single short-term, low-risk interest rate as in current official statistics, reference rates should more closely match the risk characteristics of loans and deposits. For the euro area, imputed bank output is, on average, 24 to 40 percent lower than according to current methodology. This implies an average downward adjustment of euro area GDP (at current prices) between 0.16 and 0.27 percent.
Keywords: E01; E44; O47; 330; Bank output; deposit interest rates; FISIM; loan interest rates; risk; Bank; Produktivität; Messung; Bankentgelt; Zins; Eurozone; EU-Staaten